Cocktail infographics a visual guide to creating 200 of the world's best cocktails - Spence, Jordan (Carlton Books, 2016)
This is mixology made simple! Prepare a first-class cocktail with these fun, at-a-glance infographic recipes. Each one visually displays the precise measurements and ingredients in the correct type of glass, with easy-to-see proportions. More than 200 recipes feature old favorites and modern inventions plus garnishes, from the Manhattan and Negroni to the Green Tea Martini, from coolers and coladas to slings, sours, and screws. An informative introduction gives details on equipment, bar stocking, and basic techniques.--Provided by publisher.